2013
DOI: 10.1177/1076029613493658
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Red Cell Distribution Width and Stroke in Patients With Stable Chronic Heart Failure

Abstract: In conclusion, this study demonstrated that RDW may be important hematological indices for stroke in patients with HF using propensity score analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 25 publications
0
18
0
Order By: Relevance
“…The inflammatory state and oxidative stress change the morphology, deforming force, and half-life of red blood cells, increase RDW in vivo, and cause changes in hemodynamic state [27]. RDW clinically influences the severity and prognosis of stroke, acute coronary syndrome, and other diseases [28,29]. Our study displays that preoperative RDW is associated with cognitive decline in CHD patients undergoing CABG.…”
Section: Discussionmentioning
confidence: 66%
“…The inflammatory state and oxidative stress change the morphology, deforming force, and half-life of red blood cells, increase RDW in vivo, and cause changes in hemodynamic state [27]. RDW clinically influences the severity and prognosis of stroke, acute coronary syndrome, and other diseases [28,29]. Our study displays that preoperative RDW is associated with cognitive decline in CHD patients undergoing CABG.…”
Section: Discussionmentioning
confidence: 66%
“…A study about the risk of stroke showed that RDW was an important hematologic index for stroke in patients who had cardiac insufficiency. 26 In addition, high RDW is associated with the development of stroke and is strongly associated with cardiovascular causes and all causes of death in patients who are diagnosed with stroke. 4 Another case-control study showed that RDW is a strong indicator of stroke.…”
Section: Discussionmentioning
confidence: 99%
“… 29 In a follow-up study of 153 patients who had chronic cardiac insufficiency, RDW >15.2% had sensitivity 87% and specificity 74%, and the ROC curve for RDW had an area under the curve of 0.923. 26 However, there are few studies available about the association between stroke and RDW, and there have been insufficient data about the cutoff values of RDW in the prediction of stroke. The present study showed an optimal RDW cutoff of 14% ( Table 3 ) and area under the curve of 0.760 ( Figure 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…RDW has traditionally been used for the differential diagnosis of anemia. [ 1 ] In recent years, several studies have demonstrated that increased RDW is associated with a poor prognosis in clinical settings of cardiovascular and thrombotic diseases, [ 2 ] stroke, [ 3 ] coronary artery disease, [ 4 ] diabetes mellitus, [ 5 ] hypertension, [ 6 ] metabolic syndrome (MS), [ 7 , 8 ] renal function damage, [ 5 , 9 ] and it can be a predictor of all-cause mortality in general population. [ 2 ] However, it has not been well ascertained whether anisocytosis might be a cause or a simple epiphenomenon of the underlining conditions of the above-mentioned diseases, such as inflammation, oxidative stress, under nutrition, and so forth or maybe an element of both.…”
Section: Introductionmentioning
confidence: 99%